Wolfram syndrome: A rare mimic of type 1 diabetes mellitus - Manish Gutch; Krishna Kumar Sahani; Annesh Bhattacharjee; Sukriti Kumar; Shobhit Shakya (Wolters Kluwer Medknow Publications, 2016)
Wolfram syndrome is a rare autosomal recessive disorder characterized by a constellation of disorders also known as diabetes insipidus, diabetes mellitus (DM), optic atrophy, and deafness. Patients present with DM and optic atrophy in the first decade, diabetes insipidus and sensorineural deafness in the second decade, and renal outflow tract anomalies and other neurological manifestations later in life. We report a case of a 14-year-old boy who was diagnosed with insulin-dependent DM and subsequently discovered to have optic atrophy, sensorineural hearing loss, and cardiovascular defect with a positive family history. Such cases need to be evaluated thoroughly with respect to Wolfram syndrome and its associated anomalies.